The Impact of Long-Term Particulate Matter with Diameter Micrometers ≤2.5 Exposure on Type 2 Diabetes Risk: A Meta-Analysis - Titik Anggraeni; Sarwoko; Herbasuki; Sri Sayekti Heni Sunaryanti (Journal of Epidemiology and Public Health, 2025)
Background: The rising global prevalence of type 2 diabetes (T2D) has prompted investigations into environmental risk factors beyond traditional lifestyle causes. Air pollution, particularly fine particulate matter (PM₂.₅) has emerged as a potential contributor to diabetes. This systematic review synthesizes evidence from large scale cohort studies to evaluate the association between long term air pollution exposure and T2D risk. Subjects and Method: We analyzed prospective cohort studies (2020–2025) assessing air pollution and incident T2D, sourced from PubMed, Web of Science and EMBASE using the search terms: ("air pollution" OR "PM2.5") AND ("type 2 diabetes" OR "T2D") AND ("cohort" OR "longitudinal"). We using PECO framework (Populatio= adults population; Exposure=High Exposure of PM2.5; Comparison=Low Exposure of PM2.5; Outcomes=T2D). The independent variable was Exposure of PM2.5 and dependent variable was T2D. Primary studies included were cohort manuscript published in english with year of publication between 2020 until 2025, reported adjusted hazard ratios (aHR), and the subjects was adults without diabetes at baseline. Studies were evaluated using the CASP Scale, and data were analyzed using RevMan 13. Results: This study includes 9 papers, using Cohort study designs, from China, United Kingdom, South Korea and United States. PM₂.₅ exposure consistently increased T2D risk with stronger effects at lower exposure levels (aHR = 1.24; 95% Cl = 1.07 to 1.42; p=0.004). Conclusion: Long-term PM₂.₅ exposure significantly increases T2D risk and progression